2017
DOI: 10.1523/jneurosci.2722-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Magnified Neural Envelope Coding Predicts Deficits in Speech Perception in Noise

Abstract: Verbal communication in noisy backgrounds is challenging. Understanding speech in background noise that fluctuates in intensity over time is particularly difficult for hearing-impaired listeners with a sensorineural hearing loss (SNHL). The reduction in fast-acting cochlear compression associated with SNHL exaggerates the perceived fluctuations in intensity in amplitude-modulated sounds. SNHL-induced changes in the coding of amplitude-modulated sounds may have a detrimental effect on the ability of SNHL listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 57 publications
9
69
2
Order By: Relevance
“…Although an increase in neural gain -which is thought to compensate for degraded inputs from the auditory periphery -may support the detection of weak signals (Gerken, 1979;Ernst and Moore, 2012;Chambers et al, 2016;Schlittenlacher and Moore, 2016), it may affect how a sound's regularity is represented in cortical structures, in an unhelpful way. This is in line with previous work demonstrating a correlation -with age partialed out -between neural gain enhancements and decreased speech perception performance in the presence of modulated background sound (Millman et al, 2017;Goossens et al, 2018), and with the observation that hearing loss increases the perceived magnitude of low-frequency amplitude modulation in sounds (Moore et al, 1996). This previous work together with the current findings indicate that neural function in central auditory brain structures of older people appears fundamentally altered, including, among others, a change in sensitivity to a sound's temporal regularity in auditory cortex and possibly in higher-level brain regions.…”
Section: Neural Sensitivity To Temporal Regularity In Agingsupporting
confidence: 93%
See 3 more Smart Citations
“…Although an increase in neural gain -which is thought to compensate for degraded inputs from the auditory periphery -may support the detection of weak signals (Gerken, 1979;Ernst and Moore, 2012;Chambers et al, 2016;Schlittenlacher and Moore, 2016), it may affect how a sound's regularity is represented in cortical structures, in an unhelpful way. This is in line with previous work demonstrating a correlation -with age partialed out -between neural gain enhancements and decreased speech perception performance in the presence of modulated background sound (Millman et al, 2017;Goossens et al, 2018), and with the observation that hearing loss increases the perceived magnitude of low-frequency amplitude modulation in sounds (Moore et al, 1996). This previous work together with the current findings indicate that neural function in central auditory brain structures of older people appears fundamentally altered, including, among others, a change in sensitivity to a sound's temporal regularity in auditory cortex and possibly in higher-level brain regions.…”
Section: Neural Sensitivity To Temporal Regularity In Agingsupporting
confidence: 93%
“…Previous source localizations suggest that synchronization of neural activity with low-frequency temporal regularities in sounds is strongest in auditory cortex (Herrmann et al, 2013a;Keitel et al, 2017;Millman et al, 2017). The finding of enhanced synchronization in auditory cortex for older people is consistent with the age-related gain enhancement that we observed using the adaptation paradigm.…”
Section: Neural Sensitivity To Temporal Regularity In Agingsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, whereas pure‐tone thresholds are by definition elevated in patients with sensorineural hearing loss, envelope detection thresholds are normal to better than normal (Füllgrabe, Meyer, & Lorenzi, ; Moore & Glasberg, ). Enhanced envelope coding is also evident in cortical EEG waves of people with sensorineural hearing loss and negatively correlates with speech identification in modulated noise (Millman, Mattys, Gouws, & Prendergast, ). Animal studies confirmed this finding by showing that temporal coding of the envelope, measured in single‐unit auditory nerve fibers and in auditory evoked potentials estimated to derive from the auditory midbrain, is similarly enhanced following noise‐induced hearing loss (Kale & Heinz, ; Zhong, Henry, & Heinz, ).…”
Section: Introductionmentioning
confidence: 99%